Pengembangan Nalar Kritis dalam Pendidikan Transformatif di Pesantren - Muhammad Syafiq Mughni (Journal on Education, 2024)
The era of disruption is a reality of life that undergoes changes in systems, orders, principles and values in human life. Education is no exception. Education in the 21st century is subject to a complete change. This era demands that humans coexist with information technology with which humans without limitations can access everything, only with their fingers and smartphones. This disruption in some phenomena has become a gift from God, when someone wants to attend a recitation forum he can simply open a smartphone and access it via the internet but in some phenomena, this disruption is also a disaster, because information technology is now a human being without morals, already pitting each other and slander each other. This is where critical reasoning is needed. With Critical Reasoning, humans will not just take it as it comes. They will look for the origin of the phenomena that occur. Humans will not easily conclude an incident that is visible to the eye. With descriptive analysis research method the author will examine the critical reasoning contained in the concept of Transformative education. And how to apply it in Islamic educational institutions such as Islamic boarding schools. The results of the research conducted by the author are that there are two learning cultures that have the spirit of critical reasoning and transformative education in Islamic boarding schools, namely the Bahst al-masa'il system and the sorogan Kitab kuning